Foreword: brightening our future - Costa, Manuel F. M. (2015)
Light, either sunlight or coming from the moon or the stars, emitted by the fireflies or the bulbs in our room or coming out of our TV screen, is not only one of the first main vehicles of contact with the world around us but also adds beauty and fascination to our lives. Blessing all of us, it is definitely one of the corner stones of the structure of our modern world and crucial to its development.